2023
DOI: 10.3390/horticulturae9030344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Irrigation Regimes and Nitrogen Fertilization on the Physicochemical and Bioactive Characteristics of onion (Allium cepa L.)

Abstract: The availability of water and nitrogen in the soil affect the metabolism of onion bulbs. The synthesis of metabolites and bioactive compounds are the most affected, along with the quality of the onion bulbs However, it is necessary to know the effects of different water levels and nitrogen fertilization to optimize the quality of the onion. The objective of this research was to study the effects of the different conditions of hydric stress and nitrogen fertilization during the development of onion (Allium cepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Nitrogen may play a significant role in increasing an onion's vegetative growth by enhancing its color, vigor of the leaf canopy, and meristematic activity, which contributes to the increase in cell number and cell elongation, and ultimately, its overall size [27]. These results are in harmony with those recorded by Barrales et al [28]. At 100 days after transplanting, the present study found that the lowest plant density (4 rows/ridge) yielded the best growth metrics in both growing seasons.…”
Section: Discussionsupporting
confidence: 80%
“…Nitrogen may play a significant role in increasing an onion's vegetative growth by enhancing its color, vigor of the leaf canopy, and meristematic activity, which contributes to the increase in cell number and cell elongation, and ultimately, its overall size [27]. These results are in harmony with those recorded by Barrales et al [28]. At 100 days after transplanting, the present study found that the lowest plant density (4 rows/ridge) yielded the best growth metrics in both growing seasons.…”
Section: Discussionsupporting
confidence: 80%
“…TBY ET act (5) where RCWP (kg m −3 ) is the real crop water productivity index, TBY is total bulb yields (kg), and ET act is the actual seasonal crop water consumption by evapotranspiration (m 3 ha −1 ). When considering this relation from a physical point of view, one should consider transpiration only [42,43].…”
Section: Rcwp =mentioning
confidence: 99%
“…It is widely consumed in both fresh and processed forms, including powdered, essential oil, and spice formats, owing to its distinctive aroma and flavor, which enhance food palatability [3]. The consumption of onions spans various culinary traditions and cultures, as they are valued for their nutritional properties and medicinal uses [4,5]. Onions are typically consumed either as dry bulbs at maturity or in their early green stage.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen deficiency in crops leads to decreased photosynthesis of plant leaves and growth retardation [36,37]. However, excessive application of nitrogen fertilizer reduces the tillering of crops [38]. The biological basis of monitoring crop growth via hyperspectral technology is that the difference in the internal structure and material content of crop leaves leads to a difference in spectral reflectivity, and then information on the material composition and internal structure of leaves can be obtained by studying the difference in spectral reflectance.…”
Section: Effects Of the Nitrogen Application Rate On The Spectral Cha...mentioning
confidence: 99%